Reflections on the Community Empowerment in Giving Exclusive Breastfeeding - Joni Haryanto; Yayan Sakti Suryandaru; Sylvia Dwi Wahyuni (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Less than 40 percent of children under the age of six months were given exclusive breastfeeding(WHO, 2015). Therefore, this study will fundamentally analyze qualitatively the community empowermentmodel related to exclusive breastfeeding so that the target of achieving exclusive breastfeeding can beachieved progressively and effectively. Method: The type of research used was qualitative research Thedescriptive explorative approach was chosen in accordance with the research objectives of exploring theperspectives, experiences, and expectations of breastfeeding mothers and related parties. The study wasconducted in five community health center in Surabaya. Data collection was carried out through indepthinterview with breastfeeding mothers. Total respondents was 50 people. The process of data analysis used thenine-step data interpretation method according to Colluizi. Result: there were 7 themes and 24 categories.The theme were: miss perception, benefits of breastmilk, support, obstacles, myth, cureent prohram, andexpectation. Discussion: Good cooperation between family, government, and institutions where motherswork is needed to achieve exclusive breastfeeding. in addition, massive exclusive breastmilk educationthrough social media and advertising is an urgent need.